2006
DOI: 10.1111/j.1744-7402.2006.02112.x
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity of LTCC Determined by Discontinuous Sinter‐Forging

Abstract: The sintering behavior of the commercial material Ceramtape GC, a glass‐ceramic composite, is characterized with the help of the continuum mechanical description. The sinter‐forging technique permits to determine the uniaxial viscosity of the porous ceramic body as a function of density. At an isothermal temperature of 840°C, the uniaxial viscosity varies from 0.2 to 6 GPa.s with increasing relative density from 76% to 97%. Continuous and discontinuous sinter‐forging allows the characterization of the effect i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…16 Numerous papers focus on sintering of GMC concerning various applicative aspects, [17][18][19][20][21][22] the effect of rigid inclusions on the effective composite viscosity, 23 sinter anisotropy, 24 sinter retardation, [25][26][27] as well as the coexistence of solid and liquid phases. [28][29][30][31][32] Recently, sinter-forging or loading dilatometry studies on LTCC were focused on the anisotropic constrained sintering characteristics and microstructure of LTCC [33][34][35][36] analyzing respective viscous properties and sintering stress. The macroscopic description of constrained sintering was based on the concept of the viscoelastic analogy 37,38 and related constitutive models.…”
Section: Introductionmentioning
confidence: 99%
“…16 Numerous papers focus on sintering of GMC concerning various applicative aspects, [17][18][19][20][21][22] the effect of rigid inclusions on the effective composite viscosity, 23 sinter anisotropy, 24 sinter retardation, [25][26][27] as well as the coexistence of solid and liquid phases. [28][29][30][31][32] Recently, sinter-forging or loading dilatometry studies on LTCC were focused on the anisotropic constrained sintering characteristics and microstructure of LTCC [33][34][35][36] analyzing respective viscous properties and sintering stress. The macroscopic description of constrained sintering was based on the concept of the viscoelastic analogy 37,38 and related constitutive models.…”
Section: Introductionmentioning
confidence: 99%
“…It was further established that the LTCC porous body recover its pseudo-isotropic state shortly after the removal of the load by comparing the subsequent free sintering of loaded with unloaded samples. 32 To check experimentally this hypothesis in relation to recovery, samples made of pure glass mixed with pore formers (for instance polystyrene balls) could be sintered, leaving large isolated pores in a dense matrix. Investigation of pore shape during and after loading by in situ microtomography could be correlated to the macroscopic strains.…”
Section: Discussionmentioning
confidence: 99%
“…Scherer [3] suggested that viscoelastic properties such as the uniaxial viscosity and viscous Poisson ratio could be determined from a linear viscous constitutive relationship of the mechanical response of a porous body. The uniaxial viscosity and viscous Poisson ratio as a function of the porosity are obtained by means of continuous [4], cyclic [5] and discontinuous sinter forging techniques [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…During the co-firing of asymmetric bi-layers, sintering defects such as cracks, debonding and warpage often occur due to the different densification rates that exist among the components. In order to solve this problem, the sintering behaviour of each component has to be characterized [3][4][5][6][7][8][9][10][11]. Nevertheless, few continuum mechanical approaches have been attempted in an effort to understand the co-firing processes of SOFC components.…”
Section: Introductionmentioning
confidence: 99%